2018
DOI: 10.3389/fmicb.2018.02093
|View full text |Cite
|
Sign up to set email alerts
|

Paraburkholderia phytofirmans PsJN-Plants Interaction: From Perception to the Induced Mechanisms

Abstract: The use of plant-associated bacteria has received many scientific and economic attention as an effective and alternative method to reduce the chemical pesticides use in agriculture. The genus Burkholderia includes at least 90 species including pathogenic strains, plant pathogens, as well as plant beneficial species as those related to Paraburkholderia, which has been reported to be associated with plants and exerts a positive effect on plant growth and fitness. Paraburkholderia phytofirmans PsJN, a beneficial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 99 publications
1
55
0
4
Order By: Relevance
“…Lastly, a fourth example of drought stress tolerance by bacterial volatiles involved the broad host endophyte and plant‐growth‐promoting rhizobacterium (PGPR) Paraburkholderia phytofirmans PsJN (Betaproteobacteria; Ledger et al , ). This strain was previously known to confer tolerance to a range of abiotic stresses, including salt, drought, high and low temperatures, and heavy metal contamination (Esmaeel et al , ). When investigating putative determinants of such conferred tolerance using a targeted mutagenesis approach, the authors found that none of the ‘usual suspects’ (including 1‐aminocyclopropane‐1‐carboxylate deaminase activity) accounted significantly for the observed effects.…”
Section: Direct Effects Of Bacterial Volatiles On Plant Healthmentioning
confidence: 99%
“…Lastly, a fourth example of drought stress tolerance by bacterial volatiles involved the broad host endophyte and plant‐growth‐promoting rhizobacterium (PGPR) Paraburkholderia phytofirmans PsJN (Betaproteobacteria; Ledger et al , ). This strain was previously known to confer tolerance to a range of abiotic stresses, including salt, drought, high and low temperatures, and heavy metal contamination (Esmaeel et al , ). When investigating putative determinants of such conferred tolerance using a targeted mutagenesis approach, the authors found that none of the ‘usual suspects’ (including 1‐aminocyclopropane‐1‐carboxylate deaminase activity) accounted significantly for the observed effects.…”
Section: Direct Effects Of Bacterial Volatiles On Plant Healthmentioning
confidence: 99%
“…Inoculation with the Paraburkholderia phytofirmans strain PsJN has been observed to be conducive as a stress-preventive trait as plants bearing this endophyte began to accumulate trehalose and its intermediate trehalose-6-phosphate (T6P) at 26°C (Fernandez et al, 2012). In particular, it has been reported that P. phytofirmans can affect trehalose metabolism in grapevine plants through the stimulation of T6P synthesis or the inhibition of T6P degradation (Esmaeel et al, 2018). A deep analysis of 48 genomes of Burkholderia species revealed that 161 clusters involved in secondary metabolite synthesis were likely involved in signaling between grapevine and endophytic bacteria (Esmaeel et al, 2016).…”
Section: Beneficial Effects Of Grapevine Endophytes On Abiotic Stressmentioning
confidence: 99%
“…Some compounds are important for protection because they can inhibit the growth of other bacteria and fungi (antimicrobial compounds) (Shameer and Prasad, 2018), but they also play a significant role in the mechanisms underlying signaling, defense, and gene regulation. These metabolites comprise phytoalexins (Gruau et al, 2015) and various biocide compounds (Verhagen et al, 2011; Esmaeel et al, 2018), such as HCN (Samad et al, 2017) and antibiotics (Nigris et al, 2018; Shameer and Prasad, 2018). A common trait in the group of Pseudomonas and Bacillus is HCN production (Shameer and Prasad, 2018).…”
Section: Defense Against Biotic Agentsmentioning
confidence: 99%
“…Most are considered plant commensals but few, such as the fungal Epichloë species commonly inhabiting cool-season grasses, are regarded as mutualistic, especially in high-nutrient agroecosystems (Kauppinen et al, 2016;Saikkonen et al, 2016). Plant mutualistic bacterial endophytes are less documented, but accumulating genomic and metabolomic information on bacterial genomes and modulations in plant metabolism strongly suggests they have a role in plant growth, development, and stress tolerance (Sessitsch et al, 2012;Hardoim et al, 2015;van Overbeek and Saikkonen, 2016;Esmaeel et al, 2018).…”
Section: Why Interdisciplinary Collaboration Is Neededmentioning
confidence: 99%